Kualitas Kepemimpinan Bagi Masa Depan Perpustakaan Umum - Wijatiningsih, Dwi; Zulaikha, Sri Rohyanti (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aims to determine the quality of leadership for public libraries. The research method used in this paper is qualitative. Qualitative research is a study that understands the phenomena about what is experienced by the research subject, the description uses words and language in a special natural context. The data collection technique used in this paper is the Library Research. The results of the discussion are the quality of a prospective library leader can be seen from the competencies of senior librarians, one of the appropriate leadership styles for public libraries is the transformational leadership style, and found 10 steps to become a quality leader.